Quality of working life and music in the manufacturing workplace - El-Aouar, Walid Abbas; Vasconcelos, César Ricardo Maia de; Veiga Neto, Alípio Ramos (Organizações & Sociedade, 2016)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> <!--StartFragment--> This study aimed to understand how the insertion of music in the work environment contributes to achieving Quality of Working Life (QWL), from the perspective of biopsychosocial and organisational well-being. The context where the study was conducted was the manufacturing area of a major textile company located in Natal, in the state of Rio Grande do Norte, Brazil. The use of a case study was the research strategy adopted, with exploratory and descriptive objectives. The primary data was collected through the focus group technique and semi-structured interviews were used as an additional tool. Respecting the theoretical saturation criterion, four focus groups were formed, each comprising eight randomly selected participants from the seventy-six co-workers in the sector. The data was analysed qualitatively, using the content analysis technique. Twenty-eight QWL attributes were identified. It was concluded that musical insertion provides biological, social and, above all, psychological and organisational well-being to the co-workers, contributing to achieving QWL in the work environment researched. <!--EndFragment-->